P4 A new cough remedy? patient evaluation of cough therapy group intervention. (December 2018) - Selby, J; Hull, JH; Bailey, E; Tidmarsh, B
Abstract : Introduction: Group-delivered sessions offer a simple and scalable means of providing therapy-based intervention in a constrained healthcare environment. We previously reported the efficacy of a SLT-delivered cough therapy group (CTG) in chronic refractory cough, demonstrating a reduction in cough severity. Patient perspectives for the reasons for the effectiveness of CTG have not yet been reported. The aim of this work was to review qualitative feedback from patients attending CTG, to understand patient-centered factors and thus optimise the effective delivery of this treatment. Methodology: Eligible patients with chronic cough, attributed to laryngeal hypersensitivity, attended CTG (April-June 2018), following an initial 1:1 assessment to determine suitability. Patients attended between 1 and 4 sessions with 4–8 patients per session. Sessions consisted of reviewing cough control strategies, sharing experiences, and observing patient-therapist interactions. Patients were discharged from CTG when they were satisfied with their progress in cough control, or when the SLT felt their cough modulation strategies had been fully optimised. On discharge, a detailed evaluation form (figure 1) was completed. Results: Evaluation forms were received from 41 patients (n=34 females, 83%) mean (SD) age 59 (13) years. The majority of patients reported cough duration of 0–5 years (29%), attended 2 sessions (34.1%) and reported the group sessions had been effective in reducing their cough (97.6%). The most commonly identified reasons for the effectiveness of the group were sharing and hearing advice (90%), meeting other people with cough (81%), reviewing and refreshing exercises (78%), and to keep motivated (71%). Fewer patients rated observation of the therapist working with others (56%) and the opportunity to talk further with the therapist (56%) as reasons for group effectiveness and some felt they should attend group sessions more frequently. Conclusion: Group-delivered SLT is considered by patients to be effective in reducing chronic refractory cough. The main themes reported by patients, as contributory to the effectiveness of group therapy, were interaction with other patients and revising exercises. It is important, therefore, to seek patient feedback on therapy provision to ensure services are streamlined appropriately to maximise therapeutic outcomes.